Telaah Problematika Goncangan Degradasi Intelektual dan Dekadensi Moral pada Mahasiswa: Ditinjau dari Pemikiran Al-Ghazali - Dian May Syifa; Yamani Naufal (Kartika: Jurnal Studi Keislaman, 2026)
The development of the times that occurred in this digital era gave rise to various kinds of impacts felt by all elements of society, as well as students. The inability to stem the negative impacts of technological advances has resulted in intellectual degradation and moral decadence for students in the digital era. Moving on from these problems, through a juridical approach, this research was conducted by relying on reading materials in the form of books, scientific research journals and social realities that occur in society, so as to get answers to what is the formulation of the problem. By associating the relevance of the problematical shocks of intellectual degradation and moral decadence in students in the digital era with Al-Ghazali's theory of thought, by reflecting on Al-Ghazali's theory to obtain results in the form of strategies in dealing with threats and challenges of intellectual degradation and moral decadence in students in the digital era is by realizing that the intention to study is to achieve enjoyment in this world and in the hereafter, which should be accompanied by support from an education system that applies Islamization or involves religious aspects in all knowledge given as Al-Ghazali's theory of thought